STRATEGI MANAJEMEN SDM DALAM MENINGKATKAN INOVASI KEWIRAUSAHAAN DI STARTUP DIGITAL - Kaligis, Jenny Nancy; Rawis, Joulanda Altje Meiske (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine the effectiveness of HR management strategies in increasing entrepreneurial innovation in digital startups. This research approach collects data through literature studies, which involve reading literature from various sources including books, reports, articles, and journals using qualitative and deductive approaches. The findings in this study are Entrepreneurial innovation is a key element in the success and sustainability of digital startups. To create sustainable innovation, a structured, adaptive, and talent-oriented HR management strategy is needed. This strategy covers all aspects ranging from recruitment based on potential and innovation values, sustainable competency development, innovative organizational culture, providing autonomy and responsibility, and reward and recognition systems. With the right HR management approach, startups can form a team that is able to think and act as innovators, as well as internal entrepreneurs who are ready to take the organization to the next level.